STUDI EMPIRIS KESESUAIAN LAPORAN KEUANGAN ORGANISASI NIR-LABA DENGAN PSAK 45: Gereja Advent Di DKI dan Sekitarnya - Tanggor Sihombing (Jurnal Theologia Forum STFT Surya Nusantara, 2017)
The financial statements of non-profit organizations have been set in the PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) 45. This study is devoted to the religious organization of the church, because of the religious organization nature of completeness of financial reporting is often neglected, and gradually can lead to problems in the environment church because of the lack of transparency and accountability. Another important point the need for financial statements is as management performance measurement tool of church achievement. PSAK 45 which aims to set up a nonprofit entity's financial reporting. With the standard of this report, it is expected that non-profit entity's financial statements can be more easily understood, relevance, and has a high appeal. This research is an empirical study using a questionnaire on churches represented by the church treasurer. The discussion was conducted on Adventist churches in Jakarta and surrounding areas, which includes 170 churches. Study focuses on three aspect, the financial position statements, activity report and statement of cash flows. This study shows that, first: the church aware the importance of financial report. But, statement of financial position and cash flows still have higher concern compare with the activity report. Second: Better understanding of making financial position and cash flows statement rather then activity statement. For conclusion of this study, financial records still have higher concern for church rather than as measurement of performance from financial aspect.